The effects of fiscal policy on non-oil economic growth - Fakhri Hasanov; Fuad Mammadov; Nayef Al-Musehel (Economies, 2018)
We investigate non-oil sector effects of fiscal policy in Azerbaijan over a long time period in which a recent low oil prices sample is incorporated. To obtain robust empirical findings, we use different test and estimation methods as well as address small-sample bias issues in the extended production function framework. Results show that fiscal policy has a statistically significant positive impact on the non-oil sector both in the long and short run. However, the size of the impact is small compared to the findings of earlier studies due to, we believe, the low oil-price environment and different specifications used. Azerbaijani policymakers should take measures to compensate for the declining share of oil revenues in government revenues. They may consider increasing tax rates, import and export fees, energy and other tariffs as rapid remedies to fill the budget but these measures might hurt economic development. Alternative and less harmful remedies would be optimizing government spending, strongly monitoring ongoing projects, and phasing out social and infrastructure projects, which make lower contributions to growth. Our research opens the way for further investigation of this topic for the oil exporting economies in the future.
Keywords: H50; C51; E22; 330; Azerbaijan economy; fiscal policy; non-oil sector; cointegration; error-correction modeling; Johansen approach; autoregressive distributed lags bounds testing approach